Analysis of the metabolomic profile in serum of irradiated nonhuman primates treated with Ex-Rad, a radiation countermeasure - Yaoxiang Li (Nature Portfolio, 2021)
Abstract To date, the United States Food and Drug Administration (FDA) has approved four drugs to mitigate hematopoietic acute radiation syndrome and all four are repurposed radiomitigators. There are several additional drug candidates currently under evaluation that may also be helpful for use during a widespread emergency. One possible candidate is Ex-Rad, also known as ON01210, a chlorobenzyl sulfone derivative (organosulfur compound), which is a novel, small-molecule kinase inhibitor with demonstrated efficacy in the murine model. In this study, we have evaluated the metabolomic and lipidomic profiles in serum samples of nonhuman primates (NHPs) treated with Ex-Rad after exposure to ionizing radiation. Two different dose administration schedules (Ex-Rad I administered 24 and 36 h post-irradiation, and Ex-Rad II administered 48 and 60 h post-irradiation), were used and evaluated using a global molecular profiling approach. We observed alterations in biochemical pathways relating to inflammation and oxidative stress after radiation exposure that were alleviated in animals that received Ex-Rad I or Ex-Rad II. The results from this study lend credence to the possible radiomitigative effects of this drug possibly via a dampening of metabolism-based tissue injury, thus aiding in recovery of vital, radiation-injured organ systems.